Praxias bucofonatorias para el desarrollo del lenguaje oral en los niños de 4 a 6 años - Guiscaso Lara, Gisela Fernanda (2022)
The present investigation had as objective the elaboration of a Didactic Guide on bucophonatory practices for the development of oral language of children from 4 to 6 years old, in the Pujilí canton of the Belisario Quevedo Educational Unit with the final purpose to solve the problem in the difficulties that children present in the moment of communicating, since it has been shown that children omit some sounds such as: r, s, p, d, rr, y, g, l, ll, directly influencing in the articulation of words that also affect in their academic performance, For this reason, the didactic guide is proposed with 15 workshops, that have been specially developed to work on the difficulties found in the development of language in the children, the workshops have bucophonatory exercises allowing interaction, for the application of the didactic material has been made, designed with the intention of developing and to support the verbal language. Also, the guide is based on the constructivist approach because it has the tools for the children can create meaningful learning and that they have the capacity to form at an educational and personal level, at the same time it has done the respective validation where the experts who have considered that the proposal is excellent because the activities are appropriate, concrete and according to the ages between 4 to 6 years. It has been concluded, that to improve the language development of children, it is essential to stimulate the orofacial organs by applying exercises that favor the skills of phoneme articulation, allowing efficiency in the execution of activities aimed at language development. It is recommended that the didactic guide is a support for teachers and achieve several benefits in the educational development of children, as well as the didactic materials are used for specific activities and to ease the interaction in the environment.